THE IMPACT OF DISCRIMINATION FROM LEGITIMATE POWER LEADS ANDREA SACH TO EXPERIENCE IDENTITY NEGOTIATION THROUGH FASHION IN THE DEVIL WEARS PRADA - Annisa Intan Purnama (LET: Linguistics, Literature and English Teaching Journal)
According to Ting-Toomey, the identity negotiation theory underlines the dialectical tensions and problems that immigrants and minorities face while crossing cultural boundaries from one environment to another. In individuals' numerous boundary-crossing travels, the theory emphasizes the significance of elastically negotiating sociocultural membership identity and personal identity features. Identity negotiation can work. It can be caused by personal identity and social identity. In The Devil Wears Prada by Lauren Wisberger (2003), this negotiation occurs because of discrimination in the workplace, where pressure and the work environment play a significant role in Andrea Sach's fashion changes. This film is the primary data used by researchers to dig deeper into this aspect of literature. In this study, researchers will focus on the character of Andrea Sach. Through qualitative analysis assisted by a semiotic approach, information will be obtained regarding the negotiated identity problem caused by direct discrimination by legitimate power and supported by the influence of social identity, which led Andrea to change her fashion appearance as a secretary to suit Miranda's wishes.